(untitled) - Gipson, Lawrence Henry (New York, 1962)
A book about early America that is documented with severity, written with clarity, and marked by a measured, one might almost say Franklinian, affection for the old Empire.
Keywords: United States,Hoa Kỳ; History,Lịch sử; Revolution, 1775-1783,Cuộc cách mạng 1775 - 1783